The role the expression theory on the clarity of architectural facades - Dr. Maysoon Muhi Hilal; Taghreed Flayyih Hasan (Genius Journals, 2023)
Facades that envelope architectural buildings in many ways reflect the internal function of the structure (construction, building materials, cladding). The major goal of these techniques is to express the elements of the building's internal function. and to figure out what expressionist theory is because tastes are created by the self. Tastes vary throughout time, and so does one's perception of the world. in architecture, as well as its significance in transferring the building's architectural concept to other areas was the study problem in the presence of cognitive deficits in the relationship of expressive theory in reading urban facades the research adopted a descriptive-analytical method The materials used in the external construction and the perception of the expressiveness of the exterior façade Architectural facades in a street in the city of Samarra were addressed to study and analyze 35 repulsive facades in the same street according to a table that included the effective indicators in the theory of Expressionism and its application to those facades and extract the results .
Keywords: facades; expressionist theory; architectural buildings